2021
DOI: 10.3390/vaccines9101135
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Intentions toward COVID-19 Vaccination among Spanish Adults: A Descriptive Cross-Sectional Study

Abstract: Vaccination against SARS-CoV-2 is postulated as the most effective measure to control the COVID-19 pandemic. However, the use of other protection measures is necessary to efficiently combat the spread of the virus. The aim of the present study was to determine the attitudes and intentions toward COVID-19 vaccination among non-regular social media users in Spain and to analyze how these factors could condition the acceptance of other personal protective measures once an individual has received the COVID-19 vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 78 publications
0
7
0
1
Order By: Relevance
“…However, the COVID-19 vaccination intention between these two rounds increased by 43% in 1 year [ 17 ]. At the beginning of the pandemic, COVID-19 vaccines generated much controversy due to their rapid development process, fears of health problems or lasting side effects, anti-vaccine beliefs, and the need for more information on the factors associated with not vaccinating [ 19 , 20 ]. The high levels of acceptance of the COVID-19 vaccine among the population in Spain have had a great epidemiological impact on the decrease in hospitalisation and mortality rates [ 6 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the COVID-19 vaccination intention between these two rounds increased by 43% in 1 year [ 17 ]. At the beginning of the pandemic, COVID-19 vaccines generated much controversy due to their rapid development process, fears of health problems or lasting side effects, anti-vaccine beliefs, and the need for more information on the factors associated with not vaccinating [ 19 , 20 ]. The high levels of acceptance of the COVID-19 vaccine among the population in Spain have had a great epidemiological impact on the decrease in hospitalisation and mortality rates [ 6 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the willingness of both groups to see the end of the pandemic. The vaccination campaign in Spain managed to gain the trust of the population, contrary to what happened in other European countries where there is evidence of an increase in the refusal of vaccination in the same period [ 19 ]. The increase in the intention to be vaccinated may have been reinforced, among other factors, by the implementation of the vaccination card imposed in Spain in 2021 that gave access to social, cultural, and sportive events, as well as gymnasiums, hotels, and restaurants.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies were done at the early stage of the introduction and deployment of COVID-19 vaccination. 71 72 However, these studies were done when COVID-19 vaccination had not been introduced for public use or was just being introduced. Thus, the perceptions of vaccination-related attributes such as importance, safety or side-effects and effectiveness were perhaps largely distal.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…COVID-19 vaccination intentions among populations were assessed at the early phase of the pandemic by studies across the world12–14 34–63 and in Nigeria (mostly based on social media platforms and among health workers)64–70 during the development/clinical trial stage of COVID-19 vaccines. Few studies were done at the early stage of the introduction and deployment of COVID-19 vaccination 71 72. However, these studies were done when COVID-19 vaccination had not been introduced for public use or was just being introduced.…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies were found that have investigated this key perspective. For instance, Mosteiro-Miguéns et al [31] used a survey to examine the intentions of Spanish citizens regarding COVID-19 vaccines but the respondents were not regular social media users. Despite the relevance of their study, its focus was limited to health professionals in Spain and on being a nationwide survey.…”
Section: Introductionmentioning
confidence: 99%